2021
DOI: 10.1111/dmcn.15127
|View full text |Cite
|
Sign up to set email alerts
|

External validity of the Both Hands Assessment for evaluating bimanual performance in children with bilateral cerebral palsy

Abstract: To investigate the external validity of the Both Hands Assessment (BoHA), a new test evaluating bimanual performance in children with bilateral cerebral palsy (CP), by analysing its relationship to established measurements of hand function and self-care skills.METHOD In this cross-sectional study, we recruited children with bilateral CP and manual ability corresponding to Manual Ability Classification System (MACS) levels I to III attending three habilitation units in Norway. All participants completed the BoH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Burgess et al (2021) found a strong positive correlation between self‐care capabilities and bimanual performance for 74 children (aged 8–12 years) with UCP and BCP, for children classified with MACS I–III. The strongest correlations were found among children with BCP, and this finding was further supported by the results of a cross‐sectional study of children aged 2–12.5 years by Elvrum et al (2022).…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…Burgess et al (2021) found a strong positive correlation between self‐care capabilities and bimanual performance for 74 children (aged 8–12 years) with UCP and BCP, for children classified with MACS I–III. The strongest correlations were found among children with BCP, and this finding was further supported by the results of a cross‐sectional study of children aged 2–12.5 years by Elvrum et al (2022).…”
Section: Introductionsupporting
confidence: 70%
“…The results of this study show considerable variation in PEDI scores among our cohort of preschool-aged children with CP, a finding that mirrors the rapid development of both hand function and self-care capabilities during the early years, both among children with CP and their typically developing peers (Burgess et al, 2020;Elvrum, et al, 2022;Haley et al, 1992;Klevberg et al, 2018Klevberg et al, , 2021Öhrvall et al, 2010;World Health Organization, 2007) The assessment of children's self-care capabilities is complex. Examining only manual abilities or hand use during bimanual performance does not provide sufficient information; thus, more variables should be included.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…104 105 The Both Hands Assessment (BoHA) has been adapted from the AHA, and measures how children with bilateral CP use their hands in bimanual activities. 106 Rasch measurement modelling showed strong evidence of internal construct validity 106 and scores on the BoHA are highly correlated with measures of upper limb capacity (Melbourne Assessment 2 subscales=0.48-0.83, Box and Blocks Test=0.85, n=39) 107 and measures of selfcare performance (PEDI-CAT r=0.73, n=44). 108 Paediatric Evaluation of Disability Inventory-Computerised Assessment Test PEDI-CAT is a standardised, norm-referenced assessment of independence in self-care, mobility, social cognitive and responsibility domains.…”
Section: Manual Abilitymentioning
confidence: 99%
“…The Both Hands Assessment (BoHA) has been adapted from the AHA, and measures how children with bilateral CP use their hands in bimanual activities 106. Rasch measurement modelling showed strong evidence of internal construct validity106 and scores on the BoHA are highly correlated with measures of upper limb capacity (Melbourne Assessment 2 subscales=0.48–0.83, Box and Blocks Test=0.85, n=39)107 and measures of self-care performance (PEDI-CAT r=0.73, n=44) 108…”
Section: Characterisation Of the Samplementioning
confidence: 99%